Effect of composition modification and heat treatment on the microstructure and wear resistance of plasma-sprayed nickel-based coatings for engine valves - Dykha, O.V.; Vychavka, A.A.; Babak, O.P.; Dykha, M.O.; Dytyniuk, V.O. (Problems of Tribology, 2026)
The work investigated the microstructure, phase composition and wear resistance of plasma coatings based on self-fluxing nickel alloys obtained from PG-10N-01 powder and intended for strengthening internal combustion engine valves. It was established that due to high heating and cooling rates during plasma spraying, a lamellar structure with the presence of amorphous and crystalline phases, oxide inclusions and pores is formed. It was shown that heat treatment provides partial crystallization of the amorphous phase, a decrease in porosity and an increase in the microhardness of the coating. The distribution of microhardness along the depth of the layer was studied, which is characterized by relative stability within the coating and a gradual decrease in the transition zone to the base. The effect of composition modification (introduction of ferrosilicon) on the structure formation and porosity of the coating was established. According to the results of tribological tests, an increase in wear resistance and a decrease in the coefficient of friction after heat treatment were determined. The adhesive wear mechanism caused by the structural heterogeneity of the coating is substantiated.